Forecasts for numbers of people living with dementia to 2050 and estimates for impact of smoking cessation: A modelling study in four European countries: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Ahmadi‐Abhari, Sara; Bandosz, Piotr; Shipley, Martin J; Whittaker, Hannah; Middleton, Lefkos T; Kivipelto, Miia; Brunner, Eric; Kivimaki, Mika
Abstract: Background: Forecasting dementia prevalence and the impact of preventive lifestyle interventions, requires accounting for the reduced risk of dementia and cardiovascular disease (CVD) and the concurrent increase in life‐expectancy and growing population susceptible to dementia. We aimed to forecast prevalence of dementia in Sweden, Spain, France and Poland in 2020 and 2050 assuming calendar trends in mortality rates and incidence of dementia and CVD continue the trajectories observed over the past two decades, and to estimate change in this number if elimination of cigarette‐smoking was successful. Method: We developed a Monte‐Carlo Markov model with data derived from official statistics for population numbers and mortality rates and the Survey for Health, Ageing and Retirement in Europe for baseline prevalence estimates and transition probabilities. All input parameters were age‐ and sex‐specific and were projected to the future based on observed calendar trends. Relative risks of CVD, dementia, and mortality for smoking, obtained from meta‐analyses of published studies, were used to modify transition probabilities proportionate to the change in population attributable risk fractions if smoking is eliminated by 2025. Result: Life‐expectancy at age 50 in Sweden was estimated at 31.1 years in 2020, increasing to 35.3 by 2050 if observed trajectories continue, and at 36.1 if smoking elimination was successful (Figure). Corresponding figures were 32.6, 41.7, and 44.0 years respectively for Spain; 32.5, 38.7, and 40.7 for France; and 30.3, 37.8, and 39.9 for Poland. Estimated numbers of people living with dementia in 2020 and 2050, and estimated numbers by 2050 if smoking was eliminated were 147, 000 (age‐standardized prevalence 4.2%), 223, 000 (4.1%) and 239, 000 (4.2%) respectively in Sweden (Table); 1, 090, 000 (6.8%), 2, 913, 000 (6.4%) and 3, 194, 000 (6.6%) in Spain; 998, 000 (4.8%), 2, 128, 000 (4.3%) and 2, 400, 000 (4.2%) in France; and 623, 000 (3.9%), 1, 254, 000 (3.5%) and 1, 442, 000 (3.5%) in Poland. Conclusion: Substantial increases in numbers with dementia by 2050 emphasize the importance of planning public health policies that meet the growing health‐ and social‐care needs of dementia patients in the next three‐decades. Although smoking cessation increases dementia‐free life‐years, it is unlikely to halt the increase in the numbers of dementia patients that result from concurrent increases in life‐expectancy.